Solar cabinet vacuum drying system and its drying kinetics of curry leaves - Angothu, Suneetha; Waghray , Kavita (Journal of Postharvest Technology, 2024)
A vacuum assisted solar cabinet drying system was used for drying curry leaves in the month of September and October 2021 In India. In this system a vacuum circulation system was arranged where drying will be done and vacuum is created inside the drying chamber by using a vacuum pump. In this study two drying processes were used namely solar cabinet drying (SCD) and Solar cabinet vacuum drying (SCVD) with 250, 400 and 600 mmHg is used to dehydrate the curry leaves. The quality of dried leaves were analysed for its Vitamin C and color change. The vacuum-assisted solar drying of curry leaves were of superior quality in terms of color change and Vitamin C. The average drying temperature in solar cabinet and solar cabinet vacuum drying was 54.4 ˚C and 50.53˚C respectively where itis a suitable drying temperature for fruits and vegetables. Four mathematical drying models were compared using the regression coefficients (R2), root mean square error (RMSE) and sum of square error (SSE) between the observed and predicted moisture ratios. The activation energy required for vacuum assisted solar cabinet drying of curry leaves was found to be 30.48 kJ/mol. It is found Midilli et al. and modified Henderson and Pebis model are the best fitted model to characterize drying kinetics of curry leaves.